Thailand Economic Monitor, April 2005 - World Bank (World Bank, Bangkok, 2021)
The Thai economy weathered both domestic and external shocks last year and will also do so this year. Real GDP last year grew by 6.1 percent despite higher oil prices, the Avian Influenza, and the unrest in the far South, which had adversely affected household confidence and consumption as well as foreign direct investments last year. Growth last year was partly helped by the rise in public investment after its retrenchment for 6 consecutive years. In addition, tourism revenues rebounded from the SARS scare in 2003 as reflected in the growth of exports of services, of over 10 percent last year. Some of the negative shocks such as the Southern unrest and the higher oil prices extend into this year (see Box 1 for discussion of oil price impact). In addition, the severe drought towards the end of last year and early this year would reduce agricultural production this year and could hurt farm incomes and rural consumption. The tsunami disaster in the six southern provinces late last year also has an adverse impact on tourism receipts, although to a large extent mitigated by the relief measures. With the world economy expected to slow down this year, Thailand's key export markets will also grow at slower rates. Given these negative factors, real GDP growth this year will therefore likely slow down to 5.2 percent.